Life cycle environmental impact of refurbishment of social housing. (August 2019) - Van de moortel, E; Allacker, K; De Troyer, F; Stijnen, L; Schoofs, E
Abstract: The current focus on climate change mitigation is reflected in policy goals to reduce the energy use of buildings. However, buildings are not only responsible for a large share of energy use and corresponding GHG emissions, they moreover require a lot of resources, produce a lot of waste, and emit harmful substances. In this paper, an approach is developed to investigate the most preferred renovation strategies for social housing, considering various parameters such as efficiency of the current and future heating system, service life of the heating system and insulation level of the building envelope. Moreover the reduction in life cycle environmental impact due to the replacement of heating systems by systems with increased efficiency is studied. The results show that for non-insulated buildings an increase of the thermal resistance of the building envelope is more effective than replacing the heating system while for, even poorly, insulated buildings the efficiency of the heating system is more important. A holistic Life Cycle Assessment approach is preferred to assess renovation scenarios as focussing on energy reduction might lead to an increase of the life cycle environmental impact of the building. Although this paper focuses on social housing, the approach is broadly applicable.